Bagels, Shish ka-bobs, Waffles and Salads: A Menu of Plan Types - Richard Pohlman (Oz, 1981)
Now that we have begun to depart from the Modern Movement, where are we going? Some designers are hanging bits of history on their modern frames, others are scraping away years of use to expose our roots, still others retrofit yesterday's buildings in order to discover form and technologies for tomorrow...